Pest Ants - P.G. Koehler; R.M. Pereira; J.L. Castner (EDIS)
This document provides a comprehensive overview of various ant species found in Florida, detailing their physical characteristics, nesting habits, and behaviors. It covers species such as the acrobat ant, Argentine ant, bigheaded ant, crazy ant, Florida carpenter ant, ghost ant, imported fire ant, little fire ant, native fire ant, pharaoh ant, and white-footed ant. Each section highlights unique features, such as nesting preferences, colony structure, and foraging behaviors, aiming to educate readers on identifying and managing these common pests. Date first printed: November 1992.